Tax Rebate Policy: Relevansinya dengan Kebijakan Pengelolaan Zakat di Indonesia - Syarif Hidayat Hasibuan (Universitas Islam Indonesia, 2020)
The focus of this research is centred around the issue of tax rebate policy (zakat as a tax deduction). The first research problem, how is the legal policy in regards to the management of zakat and taxes from the perspective of the history of legislation in Indonesia? Second, what is the relevance of the tax rebate policy to the zakat management policy in Indonesia? This research is a normative study with juridical and historical approach. The results of the research conclude: First, in every certain period the political and legal characteristics are very progressive, depending on the political conditions and the development of social dynamics at that time. Second, the Malaysian government places zakat as an essential component in order to alleviate poverty and the income of taxpayers is given a 100% reduction on tax payments from zakat that has been paid, while Indonesia still applies tax deduction (PKP).